2020
DOI: 10.1140/epjc/s10052-020-08475-w
|View full text |Cite
|
Sign up to set email alerts
|

New gedanken experiment on higher-dimensional asymptotically AdS Reissner–Nordström black hole

Abstract: Viewing the negative cosmological constant as a dynamical quantity derived from the matter field, we study the weak cosmic censorship conjecture for the higher-dimensional asymptotically AdS Reissner–Nordström black hole. To this end, using the stability assumption of the matter field perturbation and the null energy condition of the matter field, we first derive the first-order and second-order perturbation inequalities containing the variable cosmological constant and its conjugate quantity for the black hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Applying the transformation given in Eqs. (18), (19) and (20) to the electromagnetic potential (16) and the gravitational potential (17) of the KN metric, we can derive ω, Ãφ , Ãt (Please see App. A for the concrete expressions).…”
Section: Review Of Magnetized Kerr-newman Black Holesmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the transformation given in Eqs. (18), (19) and (20) to the electromagnetic potential (16) and the gravitational potential (17) of the KN metric, we can derive ω, Ãφ , Ãt (Please see App. A for the concrete expressions).…”
Section: Review Of Magnetized Kerr-newman Black Holesmentioning
confidence: 99%
“…In the new version of the gedanken experiment, the second-order perturbation just saves the WCCC. This approach has been applied to some other stationary black holes and the WCCC are always valid [13][14][15][16][17][18][19]. Recently, the WCCC and the second law of black hole thermodynamics have been discussed in the extended phase space [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Iyer-Wald formalism [25] and null energy condition, the second-order perturbation inequality is derived to show that WCCC is valid under the second-order approximation of the matter fields perturbation. After that, many works based on this new experiment [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] show that WCCC is applicable for other kinds of black holes. In addition, more study on the test for WCCC can be found in [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [32]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%